Vagus nerve stimulation enhances extinction of conditioned fear and modulates plasticity in the pathway from the ventromedial prefrontal cortex to the amygdala - Peña, David Frausto; Childs, Jessica E.; Willett, Shawn; Vital, Analicia; McIntyre, Christa K.; Kroener, Sven (Frontiers in Behavioral Neuroscience, 2014)
Fearful experiences can produce long-lasting and debilitating memories. Extinction of the fear response requires consolidation of new memories that compete with fearful associations. Subjects with posttraumatic stress disorder (PTSD) show impaired extinction of conditioned fear, which is associated with decreased ventromedial prefrontal cortex (vmPFC) control over amygdala activity. Vagus nerve stimulation (VNS) enhances memory consolidation in both rats and humans, and pairing VNS with exposure to conditioned cues enhances the consolidation of extinction learning in rats. Here we investigated whether pairing VNS with extinction learning facilitates plasticity between the infralimbic (IL) medial prefrontal cortex and the basolateral complex of the amygdala (BLA). Rats were trained on an auditory fear conditioning task, which was followed by a retention test and one day of extinction training. Vagus nerve stimulation or sham-stimulation was administered concurrently with exposure to the fear-conditioned stimulus and retention of fear conditioning was tested again 24 hours later. VNS-treated rats demonstrated a significant reduction in freezing after a single extinction training session similar to animals that received 5x the number of extinction pairings. To study plasticity in the IL-BLA pathway, we recorded evoked field potentials in the BLA in anesthetized animals 24 h after retention testing. Brief burst stimulation in the IL produced LTD in the BLA field response in fear-conditioned and sham-treated animals. In contrast, the same stimulation resulted in potentiation of the IL-BLA pathway in the VNS-treated group. The present findings suggest that VNS promotes plasticity in the IL-BLA pathway to facilitate extinction of conditioned fear responses.